Applying the Personal and Social Responsibility Model as a School-Wide Project in All Participants: Teachers’ Views - Manzano-Sánchez, David; Conte-Marín, Luís; Gómez-López, Manuel; Valero-Valenzuela, Alfonso (Frontiers in Psychology, 2020)
The present study aims to apply a program based on Hellison’s Teaching Personal and Social Responsibility Model (TPSR), traditionally used in Physical Education, to other educational subjects and examine the assessment of the teachers who carried it out during the 2018-2019 school year. The program was applied over eight months of one academic year and during at least 60% of the weekly class hours. Initially, 586 students participated, 429 being experimental subjects with 30 teachers, of whom 16 participated in the interviews carried out, all of them being Secondary Education teachers. We used qualitative methodology through content analysis carried out with ATLAS.ti 7.1.3. The instruments used to collect information were semi-structured recorded group interviews. The conclusion is that the Personal and Social Responsibility Model can be applied to all subjects in the curriculum and is adaptable to any content and type of student body. As a basis for future research, we suggest the application of the model by all teachers involved in the same school year and the participation of students’ families.